Character Education Model in Islamic Higher Education - Alimron Alimron; Syarnubi Syarnubi; Maryamah Maryamah (AL-ISHLAH: Jurnal Pendidikan, 2023)
The purpose of this study was to explore the character education model in the Islamic religious education study program at the Faculty of Tarbiyah and Keguruan Sciences, Raden Fatah State Islamic University Palembang. This research is descriptive qualitative research with a case study approach. This research was conducted at the Islamic Education Study Program, Faculty of Tarbiyah and Keguruan, Raden Fatah State Islamic University Palembang. Data analysis used in this research is data reduction, data presentation, and the last step ,conclusion drawing and verification. The results showed that the Islamic Education Study Program curriculum is a culture-based curriculum, which is oriented towards preparing cultured graduates, meaning that each individual is able to display behavior in accordance with human values that develop in society. The process of character building in the Islamic Education Study Program is through teaching and learning activities in the classroom. Character education is carried out through the integration of teaching and learning activities in the classroom that produce moral knowledge, moral feelings, and moral actions. In the end, the output of teaching and learning activities in the classroom is graduates with character. Therefore, it is concluded that the character education model in the Islamic Education Study Program applies an integration model, which unites the values and characters to be formed in each course.